Mapping the story: A collaborative art-based inquiry into the role of narrative in adult education - David Willis PhD; Trisha Barefield PhD; Scott Barton (Adult Education Research Conference, 2025)
This study examines the role of story and storytelling in our life-long meaning-making processes through art-based methods, creating webs of resonance between storytelling and adult education theories.
Keywords: storytelling; collaborative art-based inquiry; adult education; design maps